High Power Motor Control Electronics for a Rear Axle Steer-By-Wire System - Hallberg, Tobias; Olofsson, Joel (My University, 2015)
This thesis proposes and evaluates a solution for the power and control electronics needed for a rear-axle steer-by-wire system. The power electronics consists of transistors able to handle currents up to 400 A, gate drivers needed to drive these transistors, current measurement and heat sink design. The control electronics consists primarily of a microcontroller with protection on power supply and on peripherals attached. In addition to this, two control algorithms for motor control were investigated, six-step commutation and eld-oriented control. Six-step commutation scheme was mainly investigated in order to give the thesis workers, but also the reader, a reference tool in order to provide a better understanding of the more advance eldoriented control. During the final test of the control electronics it was shown that the power electronics was indeed able to withstand the high currents flowing, but due to problems with the control electronics no control loop was tested.
Keywords: Data- och informationsvetenskap; Informations- och kommunikationsteknik; Computer and Information Science; Information & Communication Technology